Perbedaan Pola Peningkatan Suhu Bahan Biologis dan Non-Biologis yang Dipapar Sinar Far-Infrared - Soleh, Miftahu; Sujuti, Hidayat; Widjajanto, Edi (Jurnal Kedokteran Brawijaya, 2009)
Low  power  of  Far-Infrared  Rays  (FIR)  emitted  by  artificial  radiators  have  been  used  for  many  diseases associated with blood vessels disorder.  FIR also used to  regulate  temperature  in  incubator  for  infant.  This study aims at exploring correlation pattern between FIR and temperature,  producing a biological simulator model from  a  non-biological  material for  further  research  can  be  initiated.  Differentiation  factors  between biological  and  non-biological  material  that  exposed  to  FIR  also  could  be  determined.  A  radiant  far-infrared  type T -FSR  was placed 20 cm  above the  objects (umbilicus  and gel). Then both surface  and inside  temperature  of the  objects  measured  continuously  using  Thermistor  series  D-S06  and  series  D-RB2.  Room  humidity maintained at constant levels  (60%).  This study found  a significant correlation between FIR and temperature increasing  both on the  umbilicus and on the  gel. Influence  of FIR intensity  on temperature  can be formulated into  the  formula:  T_umb_U1  =  27,6  +  0,00554  FIR  and  T_umb_U2  =  27,8  +  0,00560  FIR,  while  on  the  gel  were T_gel_U1 = 24,9 + 0,00430 FIR and T_gel_U2 = 25,0 + 0,00428 FIR.